#### Answer

1

#### Work Step by Step

We are asked to find $(f∘f)(4)$. We know that $(f∘f)(x)=f(f(x))$.
Therefore, $(f∘f)(4)=f(f(4))$.
From the first table, we see that $f(4)=3$. From the first table, we see that $f(3)=1$.
Therefore, $f(f(4))=f(3)=1$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.